Propuesta técnica para la implementación de un sistema de bombeo mecánico por sistema híbrido ESP-PCP que optimice variables operativas y energéticas en pozos productores de crudo pesado (2022)
Currently, mechanical pumping is one of the most used artificial lift systems in the production area of ​​the hydrocarbon industry, however, this system has multiple limitations and failures, which makes it a costly mechanism due to its maintenance and interventions. workover that you may need.